(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
A 55 year old male was brought dead to Lady Hardinge Medical College and its associated Hospital, New Delhi with an alleged history of being stabbed by an electric tube light on the left side of chest, following an altercation with the assailant. At autopsy a penetrating wound was found on the left side of anterior chest wall, involving the upper lobe of the left lung. A thin, slender fragment of glass from the tube light was also found in the wound. We have not found any other similar published report of stabbing by thin and fragile glass object like a tube light.